Traditional and Innovative in the Pedagogical Process Nowadays : Some Problems and Solutions - Anspoka, Zenta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There are problems analyzed in this scientific article that are connected with the ensuring of the traditional experience and purposeful innovations in the pedagogical process nowadays. Based on the empirical research data the attention is focused on the formation of student’s learning experience, application of such internal and external learning tools, which stimulate student’s thinking and responsibility for the result of their work. The ideas about purposeful integration of learning content and content of a scientific disciplineare emphasized, as well as the role of student’s language in the process of promotion of student’s thinking and socio-cultural competence, deepened understanding about human values and teacher’s experience of analytical skills to separate the scientifically proper information from the pseudoscientific information.